2006
DOI: 10.2176/nmc.46.405
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of the Pressure Setting of a Codman-Hakim Programmable Valve by a Television-Case Report-

Abstract: A 7-year-old girl presented in semicomatose condition. She had received a ventriculoperitoneal shunt using a Codman-Hakim programmable valve. Head computed tomography demonstrated hydrocephalus and head radiography showed that the pressure setting of the shunt valve had changed to 60 mmH 2 O from 40 mmH 2 O. The pressure setting was returned to 40 mmH 2 O, and she was discharged because her clinical symptoms and hydrocephalus improved. One month later, she lost consciousness again and was transported to our ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…This re-configuration mechanism allows for unrelated electronic devices with magnetic fields to change valve settings [ Table 1 ]. [ 2 3 4 11 14 ] Even amusement park rides can cause maladjustment of valves. [ 10 ] Despite these risks, programmable valves, when compared to nonprogrammable shunts, are found to be associated with a significant decrease in complications regarding over or underdrainage, as well as a reduction in overall complications.…”
Section: Introductionmentioning
confidence: 99%
“…This re-configuration mechanism allows for unrelated electronic devices with magnetic fields to change valve settings [ Table 1 ]. [ 2 3 4 11 14 ] Even amusement park rides can cause maladjustment of valves. [ 10 ] Despite these risks, programmable valves, when compared to nonprogrammable shunts, are found to be associated with a significant decrease in complications regarding over or underdrainage, as well as a reduction in overall complications.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed that even low-intensity magnetic fields from objects such as magnetic toys, television, and speakers can change the setting in some models of programmable valves. 2,4,8,9 In a recent study, the maximum gauss level produced by an iPad was 170 G, which is less than the maximum gauss level found in any of our headphones. 7 Given that the magnetic field from a headphone is much closer to the valve, there is cause for concern regarding headphones.…”
Section: Discussionmentioning
confidence: 59%
“…There are many sources of weak magnetic fields e.g. television, cell phones, or commercially available toy magnets that may influence a programmable valve in everyday life (13,7,1). The settings of the Strata valve including the Hakim valve were affected by magnetic flux densities of 6.0, 17.5, and, 40.0 mT, respectively.…”
Section: Case Descriptionmentioning
confidence: 99%